The impact of old-age pension on nutritional outcomes: Evidence from Kyrgyzstan - Yanjun Ren; Weigang Liu; Xuexi Huo; Thomas Glauben (Agribusiness, 2023)
Extensive studies have discussed the economic and welfare effects of social pensions worldwide, while scant attention has been paid to their nutritional effects, especially in emerging economies. Using multitopic longitudinal survey data of households and individuals in Kyrgyzstan covering four waves of 2012, 2013, 2016, and 2019, this study aims to examine the impact of an old-age pension on the nutritional outcomes of the elderly and shed light on their underlying mechanisms. Our empirical identification rests on a propensity score matching with difference-in-differences estimation design to address the endogeneity problem of receiving an old-age pension. Overall, the results indicate that receiving an old-age pension has a significant and negative impact on body mass index and the probability of being overweight for males, while no significant impact of the old-age pension has been observed for females. Receiving an old-age pension has no significant effect on expenditure of food consumption, calorie intake, and macronutrient intake, while it significantly reduces the ratio of protein intake to total calorie intake. We also observe significant heterogeneity in the nutritional effect of an old-age pension across various education levels and income levels; the negative nutritional effect is more salient for elderly individuals who are relatively poor or who have lower education. Our findings provide profound implications for policies targeting improving the nutritional status of rural residents in emerging economies through the implementation of the old-age pension.
Keywords: H55; I15; I38; 330; BMI; food consumption; obesity; old-age pension; overweight